Pemanfaatan Bahan Bekas Sebagai Media Pembelajaran - Andriany, Liesna; Manurung, Nurhasnah (Universitas Islam Sumatera Utara, 2014)
ABSTRACTThere are many scraps around where we live that can be used as a medium of learning. SMA Kartini Utama, SMA Teladan, and MA Alwashliyah are training place for the making of learning media of scraps. The method used is a lecture, question and answer, demonstration method, simulation and training. The goal is to increase teacherâs creativity by creating their own learning media in order to make an interesting learning process, students become active which ultimately will improve their learning outcomes.Key word: scraps, instructional media